Effective of communication using WhatsApp: industrialised building system (IBS) construction - Ahmad Pozin, Mohd Affendi; Mohd Nawi, Mohd Nasrun (AIP Publishing, 2018)
The emergence of Industry 4.0 was influenced organisation to deal with digitalisation environment. Supported with the increasing use of WhatsApp tool has received attention as a driver to enhance communication and development of digital value chain between product, environment and business partners. However, lack of research has address WhatsApp in the construction sector. Further, this research aims to investigate the quality of communication practices through WhatsApp tool ability to managing communication processes in the construction project. The approach of the semi-structured interview was conducted to gain in-depth information from 5 project managers as a respondent which experienced in managing Industrialised Building System (IBS) in Malaysian. Our result shows that WhatsApp application tool increased the efficiency of data sharing and increase quality of communication as a mechanism through which this influence exists.